SHARIAH FINANCING FOR FARMERS POVERTY REDUCTION - DAVY HENDRI (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The agricultural’s sector issues remains important, both from strategic and pragmatic sides. From the strategic side, the contribution to GDP and labor absorption in this sector is still significant. While at the pragmatic side, contrary to earlier, the poverty rate of economic actors at the sector did not experience significant improvement. Farmer’s poverty alleviation efforts, as if to see a thick wall. In the era of oil boom of the past, subsidies be the paradigm taken by government. However, because of government budget constraints, and also the absence of the private sectors role, the efforts being failed. Shariah banking have a great obligation to face this huge potential demand. Because of poor farmers was a part of the largest Islamic community itself and the maqasid Shari'ah philosophy put the protection of mankind from poverty and indigence as one of the main objectives. Nevertheless, major barriers to technical and economic, made sharia banking still not present in those efforts. Need a new paradigm which using a comprehensive approach and involve actively participation of all parties to realize those goals. To that end, this paper will try to offer that new paradigm.